Supplementation with l-arginine stabilizes plasma arginine and nitric oxide metabolites, suppresses elevated liver enzymes and peroxidation in sickle cell anaemia. Issue 2 (June 2016) - Jaja, S.I.; Ogungbemi, S.O.; Kehinde, M.O.; Anigbogu, C.N.
Abstract: The effect ofl -arginine on liver function in SCD has received little or no attention. The effect of a chronic, oral, low-dose supplementation withl -arginine (1 gm/day for 6 weeks) on some liver enzymes, lipid peroxidation and nitric oxide metabolites was studied in 20 normal (non-sickle cell anaemia; NSCA) subjects and 20 sickle cell anaemia (SCA) subjects. Ten milliliters of blood was withdrawn from an ante-cubital vein for the estimation of plasma arginine concentration ([R]), alanine aminotransaminase (ALT), aspartate aminotransaminase (AST) and alkaline phosphatase (ALP), plasma total bilirubin concentration [TB], malondialdehyde concentration [MDA] and nitric oxide metabolites concentration [NOx]. Before supplementation, ALT, AST, ALP (p < 0.05 respectively) and TB (p < 0.001) were higher in SCA subjects than in NSCA subjects. [R] and [NOx] were higher in NSCA subjects (p < 0.001 and p < 0.05 respectively). Supplementation caused greater percent increases in [R], and [NOX ] in SCA than in NSCA subjects (p < 0.001 in each case).l -Arginine caused greater percent reductions in ALT and AST in SCA subjects but greater percent reduction in ALP in NSCA subjects (p < 0.001 in each case). Changes in [MDA] and [TB] in the two groups were similar. Study shows that chronic, oral, low-dose supplementation withl -arginine improved liver function, oxidative stress, plasma arginine concentration and nitric oxide metabolites levels in NSCA and SCA subjects. Responses in SCA subjects tol -arginine were more sensitive than in NSCA subjects.